Análisis para la compensación de potencia reactiva del alimentador circuito dos perteneciente a la subestación vía Quevedo de la CENEL EP unidad de negocio Santo Domingo - Oña Velásquez, César Rolando (2016)
In distribution systems, compensation of reactive power is performed through the optimal placement of capacitor banks, primary objective being the control voltage and reducing losses, however when the compensation system is optimal you can get secondary benefits such as improved power factor, increased availability for loading by the feeder, freeing capacity transformer substation plus surcharges and penalties for low power factor. In this research the electrical parameters recorded in the feeder meter header was analyzed by power factor curves in order to determine the capacity of the capacitor bank, the same readings taken parameters as: voltages, active – reactive power, currents and power factor peak demand, medium and minimum feeder, this is in order to perform simulations in the optimum location of capacitors module CYMDIST software.